Digit Ratio, Testosterone/Cortisol Levels, and Hand Grip Strength Among Elite Iranian Wrestlers. Issue 1 (2nd January 2016) - Khanbabazadeh, Mahdi; Serajian, Abdollah; Rashidlamir, Amir
ABSTRACT: Wresting is a weight-categorized sport with many handgrips used during the competition. Many studies have reported some predictors of hand grip strength, but none of them has studied the complete hand dimensions and hormone levels in elite wrestlers. Thus, the aim of this study is to investigate the relations among digit ratios and various hand dimensions, anthropometrical characteristics, grip strength, and testosterone/cortisol levels among elite Iranian male wrestlers. For this purpose, 13 male Iranian national team wrestlers voluntarily participated in this study. The finger parameters were evaluated using the Visnapuu method, and a salivary hormonal assay was performed using an enzyme-immunoassay kit. Statistical analysis was conducted using SPSS 19. The statistical analysis of data showed significant correlations ( p < .05) between hand grip strength and hand-specific variables including finger perimeters P1, P2, P3, P5; finger lengths of the thumb, index, middle, ring and little finger lengths (TL, IFL, MFL, RFL, LFL, respectively); and the ratios of the index finger length to the little finger length (I:L), and the index finger length to the ring finger length (2D:4D), with the highest correlation being observed between the index finger length and handgrip strength ( r = 0.85, p = .001). Furthermore, additional anthropometrical characteristics including wrist girth, arm span, shoulder width (biacromial breadth) and forearm girth were found to have strong correlations with hand grip strength ( r = 0.77, r = 0.77, r = 0.73 and r = 0.70, respectively) and thus can be used as simple predictors of hand grip strength in wrestling.